(3GdMeGjI GdLfGFjI ddMb ai MQeI GdeScf (B: s (3OQGSI ebGQfI (B/ s - (3YdGA EHQGgje eMeO TghGfs; (3eOMJ YHOGdMdje QeVGf s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2017)
(3jYJHQ GdMb ai MQeI GdMjGI GdNGUI ef Cge Mbhb GdEfSGf GdJi cQSJgG eNJda GdJTQjYGJ GdOhdjI h GdOGNdjI(B: (3h GdPi ef CHQR YfGUQg MQeI GdeScf HGYJHGQ Cfg dG bjeI ddMjGI GdNGUI Gf de JTed MQeI eScf GdTNU GdPi jNdh ajg Gdi faSg HYjOG Yf Yjhf h GSeGY h JWad GdCNQjjf(B: (3h cd bjO Gh GYJOGA Ydjg gh EfcGQ ddGSJbdGd GdaQOi ai GdeLJeY h GYJOGA Ydi Cefg h cQGeJg h MQjJg(B: (3aGdGYJQGa HgPG GdMb h MeGjJg gh ef GdeejRGJ GdLhgQjI ddJTQjYGJ GdeJbOeIs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFis
(3HHdjhLQGajG(B: (3UaMGJ (B382-396s
Keywords: (3MQeI GdeScf GdNGUs; (3GdMb s; (3GdMeGjIs; (3GdeScf s; (3JaJjT GdeSGcfs; (3MQeI GdeScf ai GdJTQjYGJ GdeNJdaIs; (3GdGeGcf GdNGUIs; (3eOhfI MehQGHis; (3MQeI GdeScf ai GdTQjYI GdGSdGejIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs